Stuck in Limbo: Coping with an Unusual Circumstance as an International Medical Graduate from India - Sanjana Chetana Shanmukhappa (University Library System, University of Pittsburgh, 2020)
During the COVID-19 pandemic, medical students and graduates applying for higher education abroad face stress and anxiety. With countries under lockdown, the situation has left many wondering how they can use their time fruitfully. In this experience, I illustrate the methods I have used to gain maximum productivity in this period.